Evaluation of the use of the Moodle Platform for Fundamental Physics Lectures at University - Mutoharoh Mutoharoh; Diah Ambarwulan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
Almost all countries in the world use E-Learning as a teaching medium. Moodle is a Learning Management System (LMS), a free, open-source platform designed to assist educators in creating online courses with dynamic interaction opportunities. In this study, an evaluation of the use of Moodle was carried out, especially in fundamental physics courses (Newton's Law). Evaluation is given by distributing online questionnaires using Google Forms as a database to store answers, collect feedback, and as statistical software to provide analysis of the effect of using Moodle according to students' opinions or perspectives. The study results show that students experience problems in taking tests/quizzes using SEB due to the instability of the internet signal. One of the reasons is that students also have to join the exam zoom simultaneously. Meanwhile, the Newton's Law material provided is very contextual and rich in sample questions, including providing student feedback which is considered good.